The first record of the Asian elm aphid Tinocallis (Sappocallis) takachihoensis Higuchi, 1972 (Hemiptera: Aphididae) in the European part of Russia - Alexander I. Gubin; Vladimir V. Martynov; Tatyana V. Nikulina; Natalya I. Bulysheva (Acta Biologica Sibirica)
The Asian elm aphid Tinocallis (Sappocallis) takachihoensis Higuchi, 1972 (Hemiptera: Aphididae) was recorded for the first time in the European part of Russia. Adults and nymphs were observed in Donetsk and Rostov-on-Don in 2021, in Mariupol in 2023, in Feodosia and Berdyansk in 2024. The aphids were found in two elm species: the introduced Ulmus pumila L. and the native U. glabra Huds. These findings provide insight into the geographical expansion of this aphid species and its association with specific host plants in these regions. The overall harmfulness of the species is generally low; however, in certain cases, it has the potential to form localized populations with high densities, resulting in significant suppression of host plants.